2012
DOI: 10.1111/cod.12010
|View full text |Cite
|
Sign up to set email alerts
|

Occupational allergic contact dermatitis caused by sterile non‐latex protective gloves: clinical investigation and chemical analyses

Abstract: Contact allergy to DPG in gloves has been disputed, but, in this study, we were able to confirm the presence of DPG and cetylpyridinium chloride in the causative gloves by using a modified method for the analysis. The presence of these chemicals in gloves caused an increase in occupational contact dermatitis in surgical operating theatre personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 26 publications
6
66
1
1
Order By: Relevance
“…This indicates that glove‐related contact allergies often cause substantial work problems prompting the HCWs to seek medical care. Patch testing with extracts of the suspected glove and with the glove “as is” could have further increased the possibility of detecting relevant contact allergy to substances in gloves, but this was not possible to undertake in the setting of the present study.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This indicates that glove‐related contact allergies often cause substantial work problems prompting the HCWs to seek medical care. Patch testing with extracts of the suspected glove and with the glove “as is” could have further increased the possibility of detecting relevant contact allergy to substances in gloves, but this was not possible to undertake in the setting of the present study.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, DPG allergy was the most common rubber contact allergy, indicating increased exposure to DPG‐containing surgical gloves during the past decade. We have previously reported on 12 HCWs with occupational contact allergy to DPG in surgical gloves . Two of these HCWs participated in the present study, due to continued eczema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that despite a very low number of contact allergies to sterile rubber gloves previously reported, during recent years a substantial increase could have been observed. This tendency is likely to be explained by the increased number of contact allergies to DPG [51].…”
Section: Recent Findingsmentioning
confidence: 99%